Proporção de material orgânico no substrato artificial na produção de mudas de cafeeiro em tubetes - Dias, Ricardo (2006)
Utilization of organic materials might contribute to reduce costs of production and enhance vegetative development and quality of coffee seedlings. With the objective of evaluating the effects of the utilization of different organic materials on the standard substrate used for coffee seedlings production, (Coffe Arabic L.), an experiment was conducted at the Agrotecnical Federal Scool -EAFU in Uberlândia, MG, Brazil, in a commercial nusery of fruit-bearing and forest seedling production, from July 2005 though January 2006. It was utilized a randomized complete-block design with treatments organized as a 3 x 6 factorial arrangement with four replications. The factors studied were composed of three sources of organic materials: mature bovine manure, mature turkey bed and mature tobacco residues, all of them in six proportions of the original substrate (0, 20, 40, 60, 80 and 100%). For the fertilization of the substrate, it was utilized a slow-releasing fertilizer ( osmocote ) with the formula NPK 15-09-12 applied in homogenous mixture in the dose of 1 g of the commercial product per container. The containers utilized were rigid plastic tubettes with volumetric capacity of 120 mL. The following traits were evaluated: plant height, stem diameter, number of leaf pairs, leaf area and root and shoot dry matter weight. All data were submitted to appropriate statistical analysis. The F test was utilized to test the significance of the factors effects, considering the traditional levels of probability of 5 and 1%. In order to limit the significant difference among the sources of the organic materials, the Tukey test was used at the 5% probability level in order to compare the means. On the other hand, for the proportions of organic materials a regression analysis procedure was utilized. It was conclude that the turked bed was the organic material which presented the highest average values for all traits evaluated. The addition of 40% of turkey bed to the standard substrate, regardless of the mixture proportions, hindered seedling development; tobacco plant residue also impaired seedlings development, and from 60% lead to death all the coffee seedlings.